Experimental investigations on lignite char gasification kinetics using a pressurized drop tube reactor. (15th July 2018) - Gonzalez, Victor; Rußig, Sascha; Schurz, Martin; Krzack, Steffen; Kleeberg, Jörg; Guhl, Stefan; Meyer, Bernd
Abstract: A novel pressurized drop tube test facility, named KIVAN, for the investigation of heterogeneous gasification reactions under elevated pressures is presented. Facility configuration and possibilities of experimental test procedures are explained. The gasification behavior of a lignite char is investigated at a pressure of 21 bar. The effects of gasification temperature (1173–1323 K) and partial pressure of CO2 (5.25–15.75 bar) on the carbon conversion are determined. The measured temperature and concentration profiles inside the reactor, the settling velocity of the particles and the flow conditions along the reaction tube are used to determine kinetic parameters of the Boudouard reaction. Data on the char structural changes depending on the carbon conversion is provided and it is suitable for detailed numerical modeling of gasification processes. The determined kinetic parameters of the Boudouard reaction under these conditions are: activation energy 162 kJ·mol −1, reaction order 0.36 and pre-exponential factor 3.26·10 5  s −1  bar −036 .